DOOM: SCARYDARKFAST - Dan Pinchbeck (University of Michigan Press, 2013)
In December 1993, gaming changed forever. id Software's seminal shooter DOOM was released and it shook the foundations of the medium. This is a book about what is considered the most important first-person game ever made; about the blueprint that has defined one of the most successful genres of digital gaming. Pinbeck brings together the complete story of DOOM for the first time. It sets the scene with a discussion of the early days of first-person gaming and the video game studio system. It discusses the prototypes and the groundbreaking technology that drove the game forwards, and offers a detailed analysis of gameplay and level design. This is followed by sections on DOOM's contributions to wider gaming culture: online multiplay and the mod scene, and consideration of the many ports and sequels the game spawned. This close analysis sets the scene for an extensive discussion of the first-person gaming genre, focusing upon DOOM's status as a foundational title, using this analysis to offer a means of better understanding how the genre has developed since 1993. Pinchbeck draws extensively from primary data: from the game itself, from the massive fan culture surrounding the title, and from interviews with the developers who made it. It is this level of access to the process of development through the reflections of some of gaming's most celebrated individuals that gives the book a very particular focus and drive. It aims not only to be the definitive work on DOOM, but a snapshot of a period of gaming history, a manifesto for a development ethos, and a celebration of game culture at its best.